Interactive neurorobotics: Behavioral and neural dynamics of agent interactions - Leonardis, Eric J.; Breston, Leo; Lucero-Moore, Rhiannon; Sena, Leigh; Kohli, Raunit; Schuster, Luisa; Barton-Gluzman, Lacha; Quinn, Laleh K.; Wiles, Janet; Chiba, Andrea A. (Frontiers in Psychology, 2022)
Interactive neurorobotics is a subfield which characterizes brain responses evoked during interaction with a robot, and their relationship with the behavioral responses. Gathering rich neural and behavioral data from humans or animals responding to agents can act as a scaffold for the design process of future social robots. This research seeks to study how organisms respond to artificial agents in contrast to biological or inanimate ones. This experiment uses the novel affordances of the robotic platforms to investigate complex dynamics during minimally structured interactions that would be difficult to capture with classical experimental setups. We then propose a general framework for such experiments that emphasizes naturalistic interactions combined with multimodal observations and complementary analysis pipelines that are necessary to render a holistic picture of the data for the purpose of informing robotic design principles. Finally, we demonstrate this approach with an exemplar rat-robot social interaction task which included simultaneous multi-agent tracking and neural recordings.